Rational design, synthesis and testing of novel tricyclic topoisomerase inhibitors for the treatment of bacterial infections part 1. Issue 12 (18th September 2020) - Kirk, R.; Ratcliffe, A.; Noonan, G.; Uosis-Martin, M.; Lyth, D.; Bardell-Cox, O.; Massam, J.; Schofield, P.; Hindley, S.; Jones, D. R.; Maclean, J.; Smith, A.; et al.
Abstract : The discovery of novel tricyclic topoisomerase inhibitors (NTTI's) that address fluoroquinolone resistance. Abstract : The alarming reduction in drug effectiveness against bacterial infections has created an urgent need for the development of new antibacterial agents that circumvent bacterial resistance mechanisms. We report here a series of DNA gyrase and topoisomerase IV inhibitors that demonstrate potent activity against a range of Gram-positive and selected Gram-negative organisms, including clinically-relevant and drug-resistant strains. In part 1, we present a detailed structure activity relationship (SAR) analysis that led to the discovery of our previously disclosed compound, REDX05931, which has a minimum inhibitory concentration (MIC) of 0.06 μg mL −1 against fluoroquinolone-resistant Staphylococcus aureus . Although in vitro hERG and CYP inhibition precluded further development, it validates a rational design approach to address this urgent unmet medical need and provides a scaffold for further optimisation, which is presented in part 2.